Comparison of measurements between manual and automated eyetracking systems in patients with strabismus – A preliminary study - Janani Rajendran; Kshama Rai; Shashikant Shetty; V Mathangi (Indian Journal of Ophthalmology, 2022)
Purpose: The main objective is to test the measurements made by an automated eye-tracking system in the presence of strabismus and to compare the data with manual measurements of deviation. Methods: A prospective observational cross-sectional masked double-blinded study was conducted in a tertiary eye care center with 39 participants included in our study, aged 3–41 years. Initial screening of all participants was performed by an ophthalmologist. Ocular deviations were evaluated and compared between manual measurements and an automated eye-tracking system. The device is based on eye-tracking technology. The participants had either a congenital or acquired type of manifest or latent strabismus. Children less than 3 years of age, visual acuity <6/36, and abnormal configuration of the anterior segment were excluded from the study. Results: The prism alternate cover test (PACT) manual measurements and the automated alternate cover test for measuring horizontal deviation, the manual measurement, and the automated eye track system showed a highly positive correlation (r = 0.932, P < 0.001). The Bland Altman plot analysis shows good agreement between the two measurements, with the mean difference between the two measurements being 1.55 PD, and the 95% limit of agreement was ± 10 PD. Conclusion: The results obtained with an automated eye-tracking system correlate well with manual strabismus measurements with PACT in terms of diagnosis, precision, and accuracy, with an added benefit of lesser time consumption in performing the test in cooperative/motivated patients. Considering these aspects, patients above the age of 3 years could be assessed with the equipment.